Immune response of balb/c mice immunized with vero cell rabies vaccine and bpmpla-se adjuvant - Frazatti-Gallina, N. M.; Silva, A. B. P.; Rinaldi, D. P.; Silveri, A.; Raw, I.; Menezes, C. R. B. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The prophylaxis is an important strategy to control of human and animal rabies disease. The vaccine from Vero cellular culture for human use is efficacy and safety. However, because the technology used to produce this vaccine is expensive this product costs about ten dollars. This cost makes them impossible the use of this vaccine type in poor countries where the animal rabies control is inefficient and there many cases of human rabies. Rabies disease is responsible for about 55,000 deaths per year in the world. The objective of this study was evaluate the humoral immune response of mice (Balb/c) immunized with three different doses of Vero rabies vaccine associated with the BpMPLA-SE adjuvant. This adjuvant is a product obtained from Bordetella pertusis. Three groups of ten mice were immunized with two doses of 500μl (G1), 250μl (G2) or 125μl (G3) of Vero cell rabies vaccine (IB-lot 1103075) mixed with BpMPLA-SE (10μg/dose). Three groups control (Gc) received only rabies vaccine. The immunization occurred on days 0 and 21 and samples were taken ten days after the last dose injected and on days 60, 120 and 180 to determine the titers of neutralizing antibodies for rabies virus in BHK21 cells (RFFIT). The averages of the neutralizing antibodies titers found in the samples from each group ten days after finished the immunization were 39.2, 33.1, and 20.4 IU/ml for groups G1, G2 and G3 respectively. The results obtained on day 180 were 17.1 IU /ml (G1), 10.6 IU/ml (G2) and 9.8 (G3). In the control groups the averages of the antibodies titers were: 29.7 (Gc1), 26.9 (Gc2) and 22.2 IU/ml (Gc3) after immunization and 10.7 (Gc1), 9.5 (Gc2) and 8.5 IU/ml (GC3) on day 180 (Gc3). These data show that the adjuvant BpMPLA-SE increased the humoral immune response for rabies vaccine in Balb/c mice independent of the volume of vaccine utilized to immunize the animals. The results found are very important to reduce the number of doses and the volume of Vero cell rabies vaccine utilized in the immunization against rabies.